Curious George goes to school adapted from the Curious George film series - Rey, Margret 1906-1996; Shalleck, Alan 1929–2006 (Houghton Mifflin Company, 1989)
Curious George makes a mistake in the art room of his school but finds a missing painting in time for an open house for parents of the students
Keywords: Monkeys / Juvenile fiction; Painting / Juvenile fiction; Schools / Juvenile fiction; Monkeys / Fiction; Painting / Fiction; Schools / Fiction; Monkeys; Painting; Schools; School stories; Curious George (Fictional character) / Fiction; Bilderbuch